ANALISA KEBIJAKAN PEMERINTAH TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI DI JAWA BARAT - Lilis Lilis; Novia Clarissa; Herliani Herliani; Dikson Dikson; Jhon Wilson (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In a country has macroeconomic problems that are difficult to solve, namely inflation and unemployment. The purpose of this research is to find out a deeper explanation of government policies related to the threat of unemployment and rising inflation in West Java and the benefit is to add insight into government policies and find out how the government overcomes these problems. The research method used is quantitative observation and qualitative method by describing the actual data in the form of tables, figures, vision and mission. Based on BPS data, it can be seen that in 2021 there will be a lot of unemployment due to the COVID-19 pandemic, the policies used by the government are establishing several strategic policies, providing income tax incentives to workers, and prioritizing pre-employment cards for workers who are victims of layoffs.